2013
DOI: 10.3389/fpsyg.2013.00364
|View full text |Cite
|
Sign up to set email alerts
|

Modeling speech imitation and ecological learning of auditory-motor maps

Abstract: Classical models of speech consider an antero-posterior distinction between perceptive and productive functions. However, the selective alteration of neural activity in speech motor centers, via transcranial magnetic stimulation, was shown to affect speech discrimination. On the automatic speech recognition (ASR) side, the recognition systems have classically relied solely on acoustic data, achieving rather good performance in optimal listening conditions. The main limitations of current ASR are mainly evident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…From a computational perspective, the role of the motor system can be that of compensating for the increased ambiguity of the stimuli [29,30]. Subjects that are more impaired by increasing levels of noise should be in principle relying less on a motor compensation strategy.…”
Section: Discussionmentioning
confidence: 99%
“…From a computational perspective, the role of the motor system can be that of compensating for the increased ambiguity of the stimuli [29,30]. Subjects that are more impaired by increasing levels of noise should be in principle relying less on a motor compensation strategy.…”
Section: Discussionmentioning
confidence: 99%
“…However, human communities have richer social structures than other animals, which might have favored an open-ended instrumental use of vocal production besides ritualized display. The importance of this skill might have led to a greater investment of parental time in teaching and, we propose, to advanced forms of “tutor learning” (Canevari et al 2013). Of note, a so-called pedagogical learning environment (Csibra & Gergely 2011) might have afforded specialized teaching strategies that could be uniquely human and that greatly improve on imitation and self-teaching learning methods.…”
mentioning
confidence: 99%
“…Other studies have shown that measured articulatory data can improve speaker-independent neural network phone classifiers (Castellini et al, 2011;Canevari et al, 2013b), BN-HMM (Markov et al, 2006) and GMM-HMM phone recognizers. However the utility of measured articulatory data is largely limited by the fact that recording articulatory data is much more difficult than simply recording the audio of a speaker.…”
Section: Discussionmentioning
confidence: 99%
“…When performing the AAM (learned on msak0) on mngu0 acoustics we try to recover the AFs of a speaker from other's speech acoustics. Table 5 shows that, despite such attempt produces poor reconstruction (Ghosh and Narayanan, 2011;Canevari et al, 2013b), reconstructed AFs can still reduce flPCE and PER. Note that since the phone sets of the two datasets are different we had to map the mngu0 phone set onto the msak0 phone set.…”
Section: Cross-speaker Evaluationmentioning
confidence: 99%